CLINICAL PROFILE OF PTOSIS PATIENTS IN DR. M. DJAMIL HOSPITAL PADANG: Oral Presentation - Observational Study - Resident - Putri Amanda (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Ptosis is one of the most common upper eyelid abnormalities. Ptosis surgery is indicated when there is visual compromise. Patient clinical profile is important in diagnosing and planning treatment for ptosis correction. The aim of this study is to describe the clinical profile of ptosis surgery patient in Dr. M. Djamil Hospital Padang. Methods : This study was conducted in descriptive and retrospective manner. This research has been approved by the Medical Faculty of Andalas University research ethics committee No: 332/UN.16.2/KEP- FK/2021. All patients that were diagnosed with ptosis in Dr. M. Djamil Hospital Padang from January 2016 to December 2021 were included. Results : There were 33 patients included in this study. Most common age range was 11-20 years old (51.5%), patients were dominantly female (51.5%). According to laterality, the most common was unilateral ptosis, 21 cases (63.6%). Congenital ptosis comprises 51.5% of the cases with myogenic as the most common etiology. Severe ptosis was found in 20 cases (57.6%), poor levator function was found in 17 cases (51.5%). Levator resection was performed in 19 cases (57.6%). Thirty patients (90.9%) had MRD1 ≥2 mm post-surgery. Conclusion : Levator function is important in determining the surgical method. In severe ptosis with poor levator function, frontalis suspension is the surgery of choice. Appropriate surgical procedure in accordance to accurate pre-operative evaluation will show a good surgical result.